PERANCANGAN DAN IMPLEMENTASI JARINGAN TUNNEL DENGAN METODE PPTP PADA YAYASAN PENDIDIKAN BINA PUTERA INDONESIA - Fauzi, Ahmad; Rosyida, Susy; Syawaludin, Haekal Alief (STKIP PGRI Sumatera Barat, 2020)
In this fast-paced and instant era, everyone needs information in a fast and accurate time, therefore we need a means that can support this, that is to have a fast and stable Internet connection. However, this cannot guarantee data security, safety factor is a very important factor to consider. To resolve the security problem of data communication on public networks, with implementing the network interconnection by the Tunnel/VPN (Virtual Private Network). Yayasan Pendidikan Bina Putera Indonesia is an agency engaged in the field of education, based in Jakarta and has branches in Bekasi. This agency has best internet connection but has not implemented the interconnection network by Tunnel/VPN. Therefore, exchanging data and information among these agencies is still less efficient and effective because it still has to go through public channels using third-party application like Email and WhatsApp. This research aims to design the application of network interconnection by Tunnel/VPN using PPTP method (Point to Point Tunneling Protocol) and connecting computer networks between agencies in Yayasan Pendidikan Bina Putera Indonesia which is expected to optimize the performance of all staff at the agency.